The impact of cross-border IVF on maternal and neonatal outcomes in multiple pregnancies: Experience from a UK fetal medicine service. (July 2019) - Jaspal, Raj; Prior, Thomas; Denton, Jane; Salim, Rehan; Banerjee, Jayanta; Christoph Lees,
Abstract: Objectives: To determine whether women seeking NHS care for IVF multiple pregnancies were more likely to have sought IVF treatment overseas and whether this was associated with different maternal and neonatal outcomes. Study design: A single large tertiary centre, for perinatal care in northwest London. Sixty-five women were referred to our fetal medicine centre, between 2012–2016, with IVF conceived multiple pregnancies. Inclusion criteria: In Vitro fertilisation and conception of twins/ triplets/quadruplets. Exclusion criteria: Intra-uterine insemination, ovulation induction, Clomid-conception and singleton pregnancies. The primary outcome measure was the Country where IVF treatment was performed. The secondary outcomes measures included the specifics of IVF treatment (e.g. number of embryos transferred), subsequent pregnancy outcomes (e.g. live-births and prematurity) and neonatal outcomes (e.g. length and cost of care). Results and Conclusion: Thirty-eight women had IVF overseas; they were older and had more pre-existing medical conditions. Eleven pregnancies used donor embryos, of which ten were from overseas treatment. 75% of women treated overseas conceived a triplet or higher order pregnancy compared to fewer than 10% of women who conceived in the UK. Almost half of all women treated overseas had more than two embryos transferred. Overseas IVF pregnancies had poorer obstetric and neonatal outcomes: 24% of live born babies died in the neonatal period compared to 0% in the UK group. The average neonatal costs per baby born from overseas IVF were £20, 600: two-and-a-half times higher than for those whose mothers conceived in the UK. Higher order multiple pregnancies are greatly over-represented by those undergoing IVF in overseas clinics. These are associated with poorer obstetric and neonatal outcomes. Perhaps paradoxically, improving NHS provision of fertility services might improve outcomes for the mother and babies while reducing the long-term burden to both fertility patients and the NHS.